Big little lies. The complete second season [videorecording (DVD)]. - Kidman, Nicole, 1967-; Witherspoon, Reese, 1976-; Woodley, Shailene (Warner Bros., 2020)
On the surface, everything seems the same in the seaside town of Monterey, CA: mothers continue to dote, husbands support, children are adorable, houses are beautiful. But the night of the school fundraiser changed all that. Meanwhile, Perry's grieving mother Mary Louise Wright comes to town in search of answers after the son's death.